2020
DOI: 10.1371/journal.pntd.0008282
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-dependent susceptibility of human muscle cells to Zika virus infection

Abstract: Muscle cells are potential targets of many arboviruses, such as Ross River, Dengue, Sindbis, and chikungunya viruses, that may be involved in the physiopathological course of the infection. During the recent outbreak of Zika virus (ZIKV), myalgia was one of the most frequently reported symptoms. We investigated the susceptibility of human muscle cells to ZIKV infection. Using an in vitro model of human primary myoblasts that can be differentiated into myotubes, we found that myoblasts can be productively infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…In agreement with our findings, it was recently demonstrated that undifferentiated myoblast cells were more susceptible to ZIKV infection than are differentiated fibers ( 31 ). In neural tissues, ZIKV preferentially replicates in neural progenitor cells disrupting neurogenesis ( 32 34 ).…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with our findings, it was recently demonstrated that undifferentiated myoblast cells were more susceptible to ZIKV infection than are differentiated fibers ( 31 ). In neural tissues, ZIKV preferentially replicates in neural progenitor cells disrupting neurogenesis ( 32 34 ).…”
Section: Discussionsupporting
confidence: 94%
“…Notably, muscle regeneration is impaired in autoimmune myopathies that result from inflammatory cell activation by antibodies against signal-recognition protein or HMG-CoA reductase; the impairment, a defect in myoblast fusion and fiber formation, was associated with deficient levels of IL-4 and IL-13 (Arouche-Delaperche et al 2017 ). Thus, inflammation, its resolution and its etiology including direct muscle infection by viruses such as Zika, arboviruses, and SARS-CoV-2 (COVID-19) (Disser et al 2020 ; Filippone et al 2020 ; Legros et al 2020 ; Paliwal et al 2020 ), are important during regeneration.…”
Section: The Current Contextmentioning
confidence: 99%
“…We first assessed the effect of 2 combinations of CARN/Cr at 0.05 mM/0.05 mM or 0.1 mM/0.1 mM on muscle protein synthesis in human primary myoblasts. Myoblasts, although not fully differentiated, are growth-factor responsive and have been used in similar experiments previously [19][20][21].These doses were chosen based on the reported plasma levels for these compounds. We found that both combinations led to a significant increase in protein synthesis (Figure 1).…”
Section: Effects Of L-carnitine and Creatine On Muscle Protein Synthesis And Anabolic Signaling In Human Primary Myoblastsmentioning
confidence: 99%